SISTEM KEAMANAN BRANKAS DENGAN SECURITY GANDA MENGGUNAKAN FACE RECOGNITION DAN RFID - Salsabilla, Safira; Lutfi Toya, Leando; Ocsirendi, Ocsirendi; Sulistyo, Eko (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
A safe is a place that has been used for years to store valuable items such as important documents, gold, or money. The development of security technology is essential, especially for safeguarding valuable items and important documents in safes. Traditional safes available today are mostly conventional, meaning they still use manual locking mechanisms, which can be easily hacked, making them inefficient. This research shows that a double security system for safes is very effective for securely storing valuable items. With this system, no one except the safe owner can open the safe by guessing the pin, as is possible with conventional safes. This system requires face recognition and a wireless card (RFID) to open the safe.